Isolation, screening and characterization of biosurfactant producing microorganisms - Halim, Siti Zulaikha Suryati (2015)
Biosurfactants are amphiphilic compounds comprising of a non-polar (hydrophobic) group and a polar (hydrophilic) group which are produced by microorganisms. Biosurfactants play an important role in bioremediation processes due to their effectiveness as dispersion and bioremediation agents as well as their environmentally characteristics, such as low toxicity and high biodegradability than chemical surfactants. However, the high production cost of biosurfactants is a major drawback in the industry. Used cooking oil is one of the alternative cheap substrate for biosurfactant production. The aim of this study is to isolate, screen and characterize biosurfactant-producing bacteria from the sources of used cooking oil, contaminated soil, and palm oil mill effluent (POME). Four strains which designated as HIO 1, HIP 1, HIP 2 and HIP 3 were able to produce biosurfactant from used cooking oil. Identification using 16S rRNA reveals that HIP 1 and HIP 2 are Lysinibacillus strain while HIP 3 and HIO 1 are strains of Bacillus. HIP 3 has the biggest oil displacement area with 92.12 cm2 when tested using oil spreading assay. All the bacterial strains were identified as the biosurfactants producer.